2019
DOI: 10.1128/mbio.02370-19
|View full text |Cite
|
Sign up to set email alerts
|

Neurotropism of Enterovirus D68 Isolates Is Independent of Sialic Acid and Is Not a Recently Acquired Phenotype

Abstract: Since 2014, numerous outbreaks of childhood infections with enterovirus D68 (EV-D68) have occurred worldwide. Most infections are associated with flu-like symptoms, but paralysis may develop in young children. It has been suggested that infection only with recent viral isolates can cause paralysis. To address the hypothesis that EV-D68 has recently acquired neurotropism, murine organotypic brain slice cultures, induced human motor neurons and astrocytes, and mice lacking the alpha/beta interferon receptor were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 83 publications
(129 reference statements)
2
34
1
Order By: Relevance
“…Heparan sulfate is abundantly expressed on RD cells ( 32 ) and associated with increased virus attachment, infection efficiency, and virus replication in cells in vitro . The ability of EV-D68 to replicate in mouse neuroblastoma cells and human induced pluripotent stem cell motor neurons were independent of sialic acid recognition, although the usage of heparan sulfate was not investigated ( 30 , 33 ). In our study, unfortunately, viruses from earlier passages without E271K in VP1 were not available and an infectious clone of the clinical isolate B2/947 with the original VP1 amino acid E271 could not be recovered ( 21 ), which made a direct comparison of viruses with and without E271K in VP1 not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparan sulfate is abundantly expressed on RD cells ( 32 ) and associated with increased virus attachment, infection efficiency, and virus replication in cells in vitro . The ability of EV-D68 to replicate in mouse neuroblastoma cells and human induced pluripotent stem cell motor neurons were independent of sialic acid recognition, although the usage of heparan sulfate was not investigated ( 30 , 33 ). In our study, unfortunately, viruses from earlier passages without E271K in VP1 were not available and an infectious clone of the clinical isolate B2/947 with the original VP1 amino acid E271 could not be recovered ( 21 ), which made a direct comparison of viruses with and without E271K in VP1 not possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, since 2016, subclade B3 and to a lesser extent subclade D1 became predominant, and both were associated with neurological complications ( 16 , 27 29 ). In addition, recent studies have shown that multiple isolates from different clades are able to infect both neuronal cells and neuroblastoma cell lines ( 30 ) and that non-subclade B1 and B3 isolates were able to cause paralysis in mice after intracranial inoculation. Interestingly, isolates from the same clade differed in their ability to cause paralysis in mice ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, sialylated glycans, which are not required for the infection of neurons or astrocytes, are able to support a conformational intermediate of EV-D68, and bovine serum albumin can render some enteroviruses (e.g., echovirus 1) more permeable to small molecules. These intermediate conformations were less stable than those of the untreated viruses and were described as "primed" for transition to A-particles (32)(33)(34).…”
Section: Discussionmentioning
confidence: 92%
“…One theory for the apparent sudden emergence of EV-D68 and AFM in 2014 is a change in the virus, resulting in alterations in tissue tropism, neurovirulence, or other key pathogenic properties, and some data support this theory (42). However, studies have not identified a clear viral genetic signal that consistently correlates with neurologic disease, and data from other investigators indicate that neurotropism is not a recently acquired phenotype (44). Studies of EV-D68 tropism and replication in cell culture models, including those of neural or respiratory origin, might identify more subtle evolutionary changes that influence pathogenesis.…”
Section: Online Reportmentioning
confidence: 99%